Anxiety and Depression among Officer Cadets during the Army Basic Training in the Sri Lankan Army - Savithri Vishmika De Silva; Malathie Dissanayake (OUSL Journal)
Depression and anxiety are common mental health conditions among the Army cadet officers that have been extensively studied in the world across varying populations. They are vulnerable enough to develop such conditions due to the military training process and adjustment issues. However, mental health conditions of the Army officer cadets have seldom been studied in Sri Lanka. The current study was conducted to examine the prevalence of depression and anxiety among Army officer cadets during basic army training and associated factors. A cross-sectional study was conducted among 236 officer cadets, ranging in age from 18 to 27 years who have had the training recently. A self-reported questionnaire which included the Depression, Anxiety and Stress Scale- 21 and General Health Questionnire-30 was used to assess the prevalence of depression and anxiety. Prevalence of anxiety was 43% while the depression was reported 22% among the studied cadet officers. Findings suggest the importance of providing mental health support for these individuals during basic army training. Implementing tailored mental health support programmes that provide accessible resources, counseling services, and coping mechanism training will help officer cadets improve their mental well-being.